2013
DOI: 10.1126/scisignal.2004020
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hyperglycemia Activates an ASK1–FoxO3a–Caspase 8 Pathway That Leads to Embryonic Neural Tube Defects

Abstract: Neural tube defects result from failure to completely close neural tubes during development. Maternal diabetes is a substantial risk factor for neural tube defects, and available evidence suggests that the mechanism that links hyperglycemia to neural tube defects involves oxidative stress and apoptosis. We demonstrated that maternal hyperglycemia correlated with activation of the apoptosis signal–regulating kinase 1 (ASK1) in the developing neural tube, and Ask1 gene deletion was associated with reduced neuroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
196
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(208 citation statements)
references
References 57 publications
(108 reference statements)
9
196
1
Order By: Relevance
“…Increased pool size of lactate and TCA cycle metabolites following CB Although glucose metabolism is known to be crucial for embryonic development during CB (Hunter and Tugman, 1995;Yang et al, 2013), it remains to be fully understood how embryonic glucose metabolism changes at this stage. Our metabolome data showed that intracellular metabolites in the TCA cycle increased significantly from E8.5 to E10.5 (Fig.…”
Section: Transition Of Embryonic Metabolome Profiles During Cbmentioning
confidence: 99%
“…Increased pool size of lactate and TCA cycle metabolites following CB Although glucose metabolism is known to be crucial for embryonic development during CB (Hunter and Tugman, 1995;Yang et al, 2013), it remains to be fully understood how embryonic glucose metabolism changes at this stage. Our metabolome data showed that intracellular metabolites in the TCA cycle increased significantly from E8.5 to E10.5 (Fig.…”
Section: Transition Of Embryonic Metabolome Profiles During Cbmentioning
confidence: 99%
“…Western blotting was performed as described previously (17,57). Briefly, E12.5 embryonic hearts were sonicated in ice-cold RIPA lysis buffer (Millipore, Bedford, MA).…”
Section: Mice and Reagentsmentioning
confidence: 99%
“…Mouse models of maternal diabetes-induced embryonic malformations were described previously (18,57). Briefly, 10-wk-old WT and Ask1 Ϫ/Ϫ female mice were intravenously injected daily with 75 mg/kg STZ over 2 days to induce diabetes.…”
Section: Mice and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoblotting was performed as previously described (2,(29)(30)(31)(32)(33)(34). Briefly, ovaries from different experimental groups were sonicated in lysis buffer containing a protease inhibitor cocktail (Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%